Wage-Price Flexibility, Market Power, and the Cyclical Behavior of Real Wages, 1959-1980 - Garman, D. M.; Richards, D. J. (Quarterly Journal of Economics, 1992)
David M. Garman, Daniel J. Richards; Wage-Price Flexibility, Market Power, and the Cyclical Behavior of Real Wages, 1959–1980*, The Quarterly Journal of Ec